Efficient Blue Light Emitting Diodes Based On Europium Halide Perovskites. Issue 38 (3rd August 2021) - Luo, Jiajun; Yang, Longbo; Tan, Zhifang; Xie, Weiwei; Sun, Qi; Li, Jinghui; Du, Peipei; Xiao, Qi; Wang, Liang; Zhao, Xue; Niu, Guangda; Gao, Liang; et al.
Abstract: Flat panel displays enjoy 100 billion‐dollar markets with significant penetration in daily life, which require efficient, color‐saturated blue, green, and red light‐emitting diodes (LEDs). The recently emerged halide perovskites have demonstrated low‐cost and outstanding performance for potential LED applications. However, the performance of blue perovskite LEDs (PeLEDs) lags far behind red and green cousins, particularly for color coordinates approaching (0.131, 0.046) that fulfill the Rec. 2020 specification for blue emitters. Here, a high‐efficiency, lead‐free perovskite, CsEuBr3, is reported that exhibits bright blue exciton emission centered at 448 nm with a color coordinates of (0.15, 0.04), contributed from Eu‐5d→Eu‐4f/Br‐4p transition with an optical band gap of 2.85 eV. Further optical characterizations reveal its short excited‐state lifetime of 151 ns, excellent exciton diffusion diffusivity of 0.0227 cm 2 s −1, and high quantum yield of ≈69%. Inspired by these findings, deep‐blue PeLEDs based on all‐vacuum processing methods, which have been demonstrated as the most successful approach for the organic LED industry, are constructed. The devices show a maximum external quantum efficiency of 6.5% with an operating half‐lifetime of 50 mins at an initial brightness of 15.9 cd m −2 . It is anticipated that this work will inspire further research on lanthanide‐based perovskites for next‐generation LED applications. Abstract : Ideal blue‐light‐emitting materials should simultaneously achieve narrow emission linewidth, suitable Commission Internationale de I'Eclairage color coordinate, excellent stability, good manufacturing compatibility, as well as non‐toxic composition, which are rarely observed in previously reported materials. The design of robust and efficient lanthanide‐based halide perovskites CsEuBr3 offers one possible solution for this long‐standing challenge.